2X - 4 = - 10

add 4 to each side

2X - 4 + 4 = - 10 + 4

2X = - 6

divide each sides integers by 2

(2/2)X = - 6/2

X = - 3

------check in original equation

2(- 3) - 4 = - 10

- 6 - 4 = - 10
- 6 + (- 4) = - 10
- 10 = - 10

checks

2X - 4 = - 10

add 4 to each side

2X - 4 + 4 = - 10 + 4

2X = - 6

divide each sides integers by 2

(2/2)X = - 6/2

X = - 3

------check in original equation

2(- 3) - 4 = - 10

- 6 - 4 = - 10
- 6 + (- 4) = - 10
- 10 = - 10

checks

2X - 4 = - 10

add 4 to each side

2X - 4 + 4 = - 10 + 4

2X = - 6

divide each sides integers by 2

(2/2)X = - 6/2

X = - 3

------check in original equation

2(- 3) - 4 = - 10

- 6 - 4 = - 10

- 6 + (- 4) = - 10

- 10 = - 10

checks

2x -4 = -10 Add 4 to each side

2x = -6 Divide by the coefficient 2

x = -3

2x = -6 Divide by the coefficient 2

x = -3

2x - 4 = -10

2x = -10 + 4

2x = -6

x = -6/2

x = -3

2x = -10 + 4

2x = -6

x = -6/2

x = -3

2x - 4 = -10

2x = -10 + 4

2x = -6

x = -6 / 2

x = -3

2x = -10 + 4

2x = -6

x = -6 / 2

x = -3

2x -4+-10

2x=-10+4 - opposite

2x=-6

x=-6/2

x=-3

2x=-10+4 - opposite

2x=-6

x=-6/2

x=-3

Didn't find the answer you were looking for?